Identification and Quantitation of Neutrophil Extracellular Traps in Human Tissue Sections - Coraline Radermecker; Alexandre Hego; Philippe Delvenne; Thomas Marichal (Bio-Protocol, 2021)
Neutrophils are one of the first innate immune cells recruited to tissues during inflammation. An important function of neutrophils relies on their ability to release extracellular structures, known as Neutrophil Extracellular Traps or NETs, into their environment. Detecting such NETs in humans has often proven challenging for both biological fluids and tissues; however, this can be achieved by quantitating NET components (e.g., DNA or granule/histone proteins) or by directly visualizing them by microscopy, respectively. Direct visualization by confocal microscopy is preferably performed on formalin-fixed paraffin-embedded (FFPE) tissue sections stained with a fluorescent DNA dye and antibodies directed against myeloperoxidase (MPO) and citrullinated histone 3 (Cit-H3), two components of NETs, following paraffin removal, antigen retrieval, and permeabilization. NETs are defined as extracellular structures that stain double-positive for MPO and Cit-H3. Here, we propose a novel software-based objective method for NET volume quantitation in tissue sections based on the measurement of the volume of structures exhibiting co-localization of Cit-H3 and MPO outside the cell. Such a technique not only allows the unambiguous identification of NETs in tissue sections but also their quantitation and relationship with surrounding tissues.Graphic abstract:Graphical representation of the methodology used to stain and quantitate NETs in human lung tissue.